A performance de apresentadores e repórteres na cobertura da morte de profissionais da imprensa na tragédia da Chapecoense - Silveira, Isabel Caline Malheiros da (2020)
This dissertation analyzes how the performance of journalists who worked during the coverage of the Chapecoense tragedy was affected. Flight 2933, which belongs to LaMia company, from Bolivia, took the Chapecoense team, directors, guests and media professionals to the first final match of the South American Soccer Cup against Atlético Nacional that would be happen the next day, in Colombia. The accident occurred near the airport of Medellín, in Colombia, on November 29, 2016, when the aircraft ran out of fuel to finish the journey and fell in a mountainous region, killing 71 people, among them, 19 soccer players and 20 press professionals. Six people survived, one was a journalist. It is considered, from the perspective by Quéré (2005), that the aircraft crash was an event of great power of affectation between presenters and reporters. It is based on Goffman (2002) to explain how representations play in social life and Zumthor (2007), especially on the concept of performance. Based on these assumptions, it seeks to discuss the concept of event and relate it to the news coverage of tragedies; to reflect about the coverage of tragedies in television news, especially on the approach to death and victims; to discuss the routines of television news and the role of subjects in news programs at that moment and relate the performance from subjects in television news coverage of the event in question. In order to do this, the programs from the 29th, 30th of November and the 1st of December 2016 by the news programs Hora Um da Notícias, Jornal Hoje and Jornal Nacional by Rede Globo de Televisão are analyzed, through their own inspired analysis categories, in addition to the authors, mentioned above, in Lima (2010), Gadret (2016), Fechine (2008) and Gutmann (2014). They are: proposition of comments or judgments, presentification and facial expression, posture, body movement and speech. It was found that, in the first moments of the news, the performance of the deaths expectation prevailed, then, it passed to the incredulity that took over the news on the first day of coverage, in addition to indignation, commotion, sadness and tributes to the victims. On the second day, expectations for the survivors' health status, commotion and collective mourning prevailed. On the third, the highlight was the official disclosure of the accident reason, indignation, investigative journalism and the performance demonstration of emotions felt by the journalist himself. Considering the emotion into account as an intrinsic part of journalism, it is concluded that professionals are unable to keep their distance when they are directly affected by an event that involves the death of close people, proving that the journalist is a being involved in the world about which it informs and, therefore, there is no way to inform without neglecting emotions, whatever the news.